La imagen de los latinos en la ficción televisiva norteamericana del siglo XXI - González Aguilar, Juan Manuel; Mayagoitia Soria, Ana Martha (Historia y Comunicación Social, 2019)
The objective of this research is to analyze the image of Latinos offered in the most successful fiction series produced in the United States from the 21st century. A qualitative (content) analysis of four comedies and four dramas is carried out, in which physical, character and behavioral aspects of a total of 29 characters of different genres, ages and socioeconomic level are evaluated. It is about defining the new models from which these characters are created in the current fictions. It is demonstrated that the Latin characters have gained more relevance and protagonism in the period analyzed and that they are defined in a richer and more realistic way in their character, values and actions.
Keywords: latinos; characters; fiction; comedy; drama; stereotypes